Reactive Enamines and Imines In Vivo: Lessons from the RidA Paradigm. Issue 10 (October 2019) - Borchert, Andrew J.; Ernst, Dustin C.; Downs, Diana M.
Abstract : Metabolic networks are webs of integrated reactions organized to maximize growth and replication while minimizing the detrimental impact that reactive metabolites can have on fitness. Enamines and imines, such as 2-aminoacrylate (2AA), are reactive metabolites produced as short-lived intermediates in a number of enzymatic processes. Left unchecked, the inherent reactivity of enamines and imines may perturb the metabolic network. Genetic and biochemical studies have outlined a role for the broadly conserved reactive intermediate deaminase (Rid) (YjgF/YER057c/UK114) protein family, in particular RidA, in catalyzing the hydrolysis of enamines and imines to their ketone product. Herein, we discuss new findings regarding the biological significance of enamine and imine production and outline the importance of RidA in controlling the accumulation of reactive metabolites. Highlights: Multiple PLP-dependent α, β-eliminases use α-amino acid substrates to generate and release enamine intermediates, specifically 2-aminoacrylate (2AA). In the absence of RidA, 2AA accumulates and damages PLP-dependent enzymes through covalent modification. Rid proteins are conserved in all domains of life and split into an archetypal RidA subfamily and seven other subfamilies (Rid1–Rid7). Rid4–Rid7 proteins are missing an active-site arginine essential for the enamine/imine deaminase activity seen in the other subfamilies, suggesting additional uncharacterized roles for Rid enzymes. Non-RidA enzymes, such as Salmonella enterica cystathionine β-lyase, MetC, and the putative aspartate/glutamate racemase from S. enterica (YgeA) or Methanococcus maripaludis (MMP0739) quench 2AA in vivo, probably by producing a reactive intermediate that interacts with free 2AA.